INSTITUTIONAL AND MARKETING EFFICIENCIES OF DRAGON’S BLOOD MANAGEMENT IN BENGKULU PROVINCE, INDONESIA - Sri Lestari; Bambang Tejo Premono (Secretariat of Agency for Standardization of Environment and Forestry Instruments, 2019)
Dragon’s blood is amongst non timber forest products in which its of supply depends on its natural availability and the demand of the commodity. This study discusses institutional market, value chains and marketing efficiency of dargon’s blood. Primary and secondary data were collected by interview based on snowball sampling method. Data were analyzed descriptively and quantitatively. Institutional economics approach was used to determine institutional marketing of dragon’s blood. Results show that the relations and behavior of marketing agents of dragon’s blood will form an institutional marketing with patron-client system, because of unbalanced position in terms of economy, accessibility and information. There were four marketing channels that exist in the research area. All of these marketing channels of dragon’s blood can be categorized as efficient marketing in which an average value of marketing efficiency were 17.86%. Channel 3 is the most efficient marketing channel with the smallest efficiency value of 12.86% and high farmer share (62.86%): penjernang – dragon’s blood traders at the village level – urban merchants in the district level – wholesalers at the province level – exporter. This result indicates that the most efficient marketing channel was the channel where the collectors sell dragon’s blood in the form of resin.